The Everyday Life Experiences and Coping Processes of Highly Skilled Immigrants in Germany - Fatma Güzin Ağca Varoğlu (Journal of Economy Culture and Society)
Negative attitudes against migrants of Turkish origin in Germany strain relations within society and constitute the underlying reasons for the increase of everyday discrimination. Migration due to academic concerns makes up one of the many migration waves between Turkey and Germany. In this study semi-structured interviews were conducted with 10 participants, who were considered as highly skilled immigrants both due to their migration for postgraduate studies and their possession of a particular social-cultural capital, evaluating their everyday experiences and coping processes in this regard using the content analysis from a range of qualitative research methods. PhD students differ with their specific purposes and conditions of migration from other migrant generations representing the largest minority in Germany. Yet, despite this distinction, their everyday experiences and stereotypes show similarities with the members of the minority society. However, they differentiate from their respective minority group with regard to their coping processes. The main questions this article deals with are the experiences of these actors, the tactics they have developed through their perceived stereotypes and the process of belonging that is manifested in this regard.